The Role of AR Technology in the Era of Pandemic Marketing - Mitrovic, Ksenija; Jakšić, Anja; Spajić, Jelena (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The consequences of the global pandemic have accelerated the digital transformation and created a new business environment. Adapting to the circumstances, brands have shifted their communication and sales on the online channel. Despite the growth of online shopping, the inability to test products is known to be one of the main obstacles to choosing this channel. Limited access to stores during the pandemic has forced brands to choose alternative ways to display and test products. Creating business models based on virtual technologies is recognized as a chance to engage consumers in the era of pandemic marketing, when the importance of digital experiences is growing. In such conditions, the tool that enables virtual try-on, supported by augmented reality (AR) technology, has experienced expansion. The paper analyzes the usage of AR technology and its virtual try-on function. An overview of virtual solutions in different industries is given. In addition to the utilitarian, hedonistic value of interaction with such tools is also recognized, making the virtual try-on feature more than a pandemic trend.